Penanaman Nilai-nilai Akhlakul Karimah Siswa di MI Sudirman Mundu Program Khusus (Tinjauan Aksiologi) - Mujiburrohman, Mujiburrohman; Miftahurohman, Miftahurohman (TSAQOFAH, 2025)
This research is motivated by the existence of students who have poor morals, such as students who still like to come late, don't respect teachers, don't picket class, don't do daily tests independently and still don't care about their friends. The indicators of akhlakul karimah are respect for elders, discipline, honesty and generosity. The aim of this research is to find out how to instill moral values ​​at MI Sudirman Mundu Gondangrejo Special Program, Karanganyar. This type of research is descriptive qualitative research. Data collection methods use observation, interviews and documentation. Data analysis and processing is taken from when the researcher is in the field and after collecting data from the field. The results of the research concluded that the instilling of students' moral values ​​in the MI Sudirman Mundu Special Program was good. After efforts to instill good morals in students, the children's attitudes have begun to change. Students begin to respect the teacher, are disciplined, honest and care about their friends. Instilling morals in students is carried out by being a role model, providing advice, habituation, and providing a deterrent effect. The factors that influence the cultivation of students' morals are divided into 2 supporting factors, namely IMTAQ habits which are carried out every day and cooperation between fellow teachers in developing students' morals. The inhibiting factors are students' lack of awareness of good morals, lack of attention from parents, and the community environment, especially the social environment. The solutions used by teachers to overcome obstacles in instilling moral values ​​in students are providing advice, actively maintaining good relationships with parents/guardians of students and teachers always collaborating with other teachers.